Computer simulations of thermal tissue remodeling during transvaginal and transurethral laser treatment of female stress urinary incontinence. Issue 2 (22nd February 2016) - Hardy, Luke A.; Chang, Chun‐Hung; Myers, Erinn M.; Kennelly, Michael J.; Fried, Nathaniel M.
Abstract : Background and Objectives: A non‐surgical method is being developed for treating female stress urinary incontinence by laser thermal remodeling of subsurface tissues with applied surface tissue cooling. Computer simulations of light transport, heat transfer, and thermal damage in tissue were performed, comparing transvaginal and transurethral approaches. Study Design/Materials and Methods: Monte Carlo (MC) simulations provided spatial distributions of absorbed photons in the tissue layers (vaginal wall, endopelvic fascia, and urethral wall). Optical properties (n, μa, μs, g) were assigned to each tissue at λ  = 1064 nm. A 5‐mm‐diameter laser beam and incident power of 5 W for 15 seconds was used, based on previous experiments. MC output was converted into absorbed energy, serving as input for finite element heat transfer simulations of tissue temperatures over time. Convective heat transfer was simulated with contact probe cooling temperature set at 0°C. Variables used for thermal simulations (κ, c, ρ) were assigned to each tissue layer. MATLAB code was used for Arrhenius integral thermal damage calculations. A temperature matrix was constructed from ANSYS output, and finite sum was incorporated to approximate Arrhenius integral calculations. Tissue damage properties (Ea, A) were used to compute Arrhenius sums. Results: For the transvaginal approach, 37% of energy was absorbed in the endopelvic fascia target layer with 0.8% deposited beyond it. Peak temperature was 71°C, the treatment zone was 0.8‐mm‐diameter, and 2.4 mm of the 2.7‐mm‐thick vaginal wall was preserved. For transurethral approach, 18% energy was absorbed in endopelvic fascia with 0.3% deposited beyond the layer. Peak temperature was 80°C, treatment zone was 2.0‐mm‐diameter, and 0.6 mm of 2.4‐mm‐thick urethral wall was preserved. Conclusions: Computer simulations suggest that transvaginal approach is more feasible than transurethral approach. Lasers Surg. Med. 49:198–205, 2017. © 2016 Wiley Periodicals, Inc.